Relationship Factors Associated with HIV Risk Among a Sample of Gay Male Couples - Mitchell, Jason W. (2012)
More HIV prevention research is needed to better understand how relationship factors may affect sexual risk behaviors among gay male couples. Our cross-sectional study collected dyadic data from 144 gay male couples to examine which relationship factors and characteristics were associated with men having UAI with a secondary sex partner. We targeted male couples by using a variety of recruitment strategies. Multilevel random-effects logistic regression modeling was used to examine which factors were predictive of men in gay couples who had UAI with a secondary sex partner. Analyses revealed that men were less likely to have had UAI with a secondary sex partner if they reported being in a strictly monogamous relationship, receiving an HIV test within the previous three months, and being committed to their sexual agreement. Future HIV prevention interventions must consider how relationship factors may influence sexual risk behaviors among gay male couples.